ASEAN’S ROLE IN THE REGIONAL COMPREHENSIVE ECONOMIC PARTNERSHIP (RCEP) FORMATION TO ENHANCE REGIONAL ECONOMIC INTEGRATION - Adila, Shofiya; Suryadipura, Dadan, S.Ip., M.Ipol. (Global: Jurnal Politik Internasional, 2023)
The RCEP agreement is currently the largest free trade agreement involving ten ASEAN member countries and their trading partners, comprising around 30% of the world’s GDP. As an international organisation in the Southeast Asian region, ASEAN has the desire to increase its regional economic integration, one of which is through the RCEP agreement. This article aims to discuss how ASEAN attempts to enhance regional economic integration through its roles during the RCEP agreement's formation process. The author uses role theory by Lisbeth Aggestam (2006), which elaborates on four role concepts: role expectations, role conception, role performance, and role-set. This research uses qualitative methods of analysing documents, including books, journals, and other supporting data. Through this research, we found that ASEAN has fulfilled its various roles as an international organisation during the RCEP formation process in order to make this agreement possible, including meeting external expectations, actualising ASEAN’s goals, its responsivity in fickle conditions, and implementing the ASEAN centrality concept. This research shows that ASEAN has succeeded in fulfilling its role as an international organisation to enhance regional economic integration by establishing the RCEP agreement.